PENGGUNAAN GADGET TERHADAP PERKEMBANGAN PSIKOSOSIAL ANAK USIAPRASEKOLAH DI TK NEGERI PEMBINA LIMBOTO KABUPATEN GORONTALO - Firmawati Firmawati; Nur Uyuun I. Biahimo; Rusliah Jainul Abd Kamba (Zaitun (Jurnal Ilmu Kesehatan), 2019)
Gadget is  an English term that means a small electronic device with various special functions. The psychosocial development of children at the preschool stage is the basis of a person's psychosocial condition as an adult. The objective of research was to determine The correlation of The Use of Gadgets on Psychosocial Development in Preschool Children at TK Negeri Pembina Limboto. Sampling technique used Total Sampling with samples are 100 respondents.the design used analytic descriptive with cross sectional study. Based on the result obtained nilai p value = 0,003 means small then α = 0,05 (Chi square test). Concluded there is correlation of the use of gadgets on psychosocial development in preschool children at TK Negeri Pembina Limboto, Limboto District. Based on the result above the researcher suggests that kindergartens be able to introduce traditional games and improve communication and interaction between teacher and student.